Peripheral endothelial dysfunction in myalgic encephalomyelitis/chronic fatigue syndrome - Nadja Scherbakov; Marvin Szklarski; Jelka Hartwig; Franziska Sotzny; Sebastian Lorenz; Antje Meyer; Patricia Grabowski; Wolfram Doehner; Carmen Scheibenbogen (ESC Heart Failure)
Abstract Aims Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a complex multisystem disease. Evidence for disturbed vascular regulation comes from various studies showing cerebral hypoperfusion and orthostatic intolerance. The peripheral endothelial dysfunction (ED) has not been sufficiently investigated in patients with ME/CFS. The aim of the present study was to examine peripheral endothelial function in patients with ME/CFS. Methods and results Thirty‐five patients [median age 40 (range 18–70) years, mean body mass index 23.8 ± 4.2 kg/m2, 31% male] with ME/CFS were studied for peripheral endothelial function assessed by peripheral arterial tonometry (EndoPAT2000). Clinical diagnosis of ME/CFS was based on Canadian Criteria. Nine of these patients with elevated antibodies against β2‐adrenergic receptor underwent immunoadsorption, and endothelial function was measured at baseline and 3, 6, and 12 months follow‐up. ED was defined by reactive hyperaemia index ≤1.81. Twenty healthy subjects of similar age and body mass index were used as a control group. Peripheral ED was found in 18 of 35 patients (51%) with ME/CFS and in 4 healthy subjects (20%, P < 0.05). Patients with ED, in contrast to patients with normal endothelial function, reported more severe disease according to Bell score (31 ± 12 vs. 40 ± 16, P = 0.04), as well as more severe fatigue‐related symptoms (8.62 ± 0.87 vs. 7.75 ± 1.40, P = 0.04) including a higher demand for breaks [9.0 (interquartile range 7.0–10.0) vs. 7.5 (interquartile range 6.0–9.25), P = 0.04]. Peripheral ED showed correlations with more severe immune‐associated symptoms (r = −0.41, P = 0.026), such as sore throat (r = −0.38, P = 0.038) and painful lymph nodes (r = −0.37, P = 0.042), as well as more severe disease according to Bell score (r = 0.41, P = 0.008) and symptom score (r = −0.59, P = 0.005). There were no differences between the patient group with ED and the patient group with normal endothelial function regarding demographic, metabolic, and laboratory parameters. Further, there was no difference in soluble vascular cell adhesion molecule and soluble intercellular adhesion molecule levels. At baseline, peripheral ED was observed in six patients who underwent immunoadsorption. After 12 months, endothelial function had improved in five of these six patients (reactive hyperaemia index 1.58 ± 0.15 vs. 2.02 ± 0.46, P = 0.06). Conclusions Peripheral ED is frequent in patients with ME/CFS and associated with disease severity and severity of immune symptoms. As ED is a risk factor for cardiovascular disease, it is important to elucidate if peripheral ED is associated with increased cardiovascular morbidity and mortality in ME/CFS.